Improved Performance of Rechargeable Li‐O2 Batteries with Plate‐like SnS2 as Efficient Cathode Catalyst. Issue 22 (14th September 2018) - Hou, Xiaoyan; Mao, Ya; Yang, Jun; Ma, Zi‐Feng; Yuan, Xianxia
Abstract: Layer‐structured SnS2 powders with plate‐like and flower‐like morphologies have been successfully synthesized through a facile hydrothermal method with different sources of sulfur. Their potential application as cathode catalysts of rechargeable Li−O2 batteries were electrochemically evaluated and analyzed with diverse physicochemical techniques. The results reveal that both SnS2 materials are capable of catalyzing oxygen reduction reaction as well as oxygen evolution reaction in the cathode of Li−O2 batteries, while the plate‐like ones perform much better. Moreover, the performance of SnS2 is also comparatively discussed with the opponent of tin oxides to identify the superiority of transition metal sulfides to transition metal oxides as cathode catalysts of Li−O2 batteries. Abstract : Flower power : plate‐like and flower‐like SnS2 particles are synthesized and tested for their performance as cathode material in Li−O2 batteries. Both materials perform better than SnO2 as cathode, while plate‐like SnS2 shows superior performance to flower‐like SnS2 .